Marketing strategy of the brand NIVEA aiming at consumers aged 20-40 on the Czech market - Kalmárová, Dominika; Průša, Přemysl, 1980-; Bahles, Michael; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis examines how Czech consumers aged 20 to 40 perceive the NIVEA brand and its marketing communication. The theoretical part includes trends in the cosmetics industry, consumer behaviour and a detailed look at the NIVEA brand, including its history, portfolio, sustainability efforts and marketing strategies. The practical part includes both quantitative and qualitative research focusing on consumer attitudes, purchasing behaviour and brand expectations. The thesis offers an insight into how the NIVEA brand is perceived on the Czech market and how its communication is in line with consumer preferences and current trends.
Vedoucí práce: Přemysl Průša
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses